Radiotherapy Alone or With Chemotherapy in the Management of Carcinoma of the Supraglottic Larynx: A 25-Year Community Hospital Experience. (September 2018) - Rao, Amy R.; Jones, Daniel A.; Mendenhall, Charles M.; Rizvi, Syed N.; Kirwan, Jessica; Morris, Christopher G.; Johns, Andrew; McAfee, William J.; Mendenhall, William M.
Abstract : Objectives: The purpose of this study was to retrospectively review outcomes for patients treated with definitive radiotherapy for carcinoma of the supraglottic larynx at a community hospital and to compare our results with the literature. Materials and Methods: Treatment records of 46 patients with localized carcinoma of the supraglottic larynx treated from January 1987 through January 2012 were reviewed. Overall, 18 (39%) presented with stage I or II disease, whereas 28 (61%) presented with stage III to IV. In total, 30 patients (65%) were treated using hyperfractionation, whereas 16 (35%) received once-daily fractionation. Twelve patients (26%) received concurrent chemotherapy with weekly cisplatin. The Kaplan-Meier method was used to assess outcomes. Results: The median follow-up for the living patients was 6.7 years (range, 1.7 to 23.1 y). At 5 years, the local-regional control (LRC), ultimate LRC, laryngeal preservation, and overall survival (OS) rates were 70%, 82%, 65%, and 53%, respectively. At 5 years, disease-free survival and cause-specific survival rates were 75% and 76%, respectively. The 5-year OS rates by American Joint Committee on Cancer stage were as follows: I to II, 61%; III, 51%; and IV, 44%. For those receiving concurrent chemotherapy, there was no improvement in 5-year LRC (83% vs. 66%; P =0.4081) or OS (55% vs. 50%; P =0.7697). For those receiving hyperfractionation, there was no improvement in 5-year LRC (75% vs. 63%; P =0.3369) or OS (55% vs. 50%; P =0.4161). Conclusions: Our outcomes are similar to those reported in the literature. Neither hyperfractionation nor chemotherapy appeared to confer a benefit for disease control or OS possibly owing to small sample size and the inherent bias of a retrospective review.